BLENDED LEARNING MODELS: COMBINING TRADITIONAL AND DIGITAL APPROACHES - Ablyakimova Refide; Toshpulatova Ismigul (Journal of Higher Education and Academic Advancement, 2024)
This article describes the selection of the most effective innovative methods and technologies in the modern higher education system, the importance of electronic education in the higher education system, the concept of mixed education and its models, given in the literature by a number of local and foreign scientists.